Analisis SWOT Potensi Zakat Produktif di Indonesia: Studi Pendekatan NVivo dan Literature Review - Doni Yusuf Bagaskara; Rohmadi Rohmadi (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2025)
The main objective of this study is to conduct a SWOT analysis on the potential of Productive Zakat in Indonesia using the NVivo method. The research methodology involves qualitative analysis along with the NVivo approach and a review of existing literature. The data analysis methods consist of: (1) categorizing news articles based on SWOT analysis using NVivo 14 software; (2) creating visual representations through hierarchical diagrams and examining the relationship between media articles using SWOT analysis; (3) generating word clouds to identify commonly discussed topics in media articles; and (4) assessing the significance of correlations among media articles related to "Productive Zakat". The findings indicate that media articles mostly focus on the opportunities and strengths of Productive Zakat, while challenges and weaknesses are less frequently addressed. This research suggests that the SWOT analysis and literature review offer valuable insights for enhancing the management of Productive Zakat in the future.